Estimates of energy intake and expenditure in elite female Touch players assessed during an international tournament - Marsh, N.; Twist, C.; Dobbin, N.; Curtis, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Touch Rugby (Touch) is an intermittent high-intensity sport. At an international level, players are required to compete in up to three 40-minute matches per day over four consecutive days. Players must be adequately fuelled to achieve optimum performance and recovery. Studies are yet to estimate the total daily energy expenditure (TDEE) and energy intakes (EI) of elite Touch players. Therefore, this study aimed to assess the TDEE, EI and macronutrient intakes of elite female Touch players during an international competition. Sixteen elite female Touch players (age: 27.4 ± 6.2 years, stature: 1.63 ± 0.06 m, body mass: 60.0 ± 6.5 kg, BMI: 22.5 ± 2.3 kg.m-2) from the 2016 England Women`s squad were recruited. Participants wore GPS technology during matches and accelerometers outside of matches over four consecutive days at the 2016 European Touch Championships. These data were combined with estimates of resting energy expenditu re to estimate TDEE. Participants completed four-day self-reported food diaries to estimate EI and macronutrient intakes. TDEE (43.6 ± 3.1 kcal.kg-1) was not different (p > 0.05) from EI (39.9 ± 9.4 kcal.kg-1). Carbohydrate intakes (4.4 ± 0.6 g.kg-1, 45% total kcal) were below (p < 0.05) the current recommended intakes (6-10 g.kg-1). Protein (2.0 ± 0.8 g.kg-1, 20% total kcal) and fat (1.7 ± 0.5 g.kg-1, 37% total kcal) intakes were in line with the recommendations (protein: 1.2-2g.kg-1, fat: 20-35% total kcal) whereas saturated fat intakes (13 ± 3% total kcal) were greater (p < 0.05) than the recommendations (10% total kcal). For the first time, this study reports that elite female Touch players maintain energy balance during an international tournament. Carbohydrate intakes appear insufficient when compared to the current sports nutrition recommendations, but future work should look to establish whether these recommendations are applicable to Touch. Further research is also required to determine if findings here are representative of elite level Touch or unique to the cohort studied.